Symbolic Interactionism of Tahilalats' Collaborative Comic "Nyaman dan Sederhana" in the Culture of Globalization in Indonesia - Shinta, Diesta Noor (DeKaVe, 2024)
Human existence in the current era of globalization is shown by the number of followers, likes, and responses in social media accounts that have become part of human life. The great desire of people from teenagers to adults to pursue fame and popularity through social media is a concern both individually and in the surrounding environment. In the Tahilalats collaboration comic with ABC Coffee with the caption "Nyaman dan Sederhana" posted on Instagram, conveys a message of unrest related to the problem of social media influence on society. In the story there is the concept of Stoicism Marcus Aurelius with the narrative that it is not bad to be an ordinary person who is able to control himself. This comic also reflects the influence of global culture that is relevant to everyday life in Indonesian society. The purpose of this research is to analyze the message conveyed through the comic about simplicity to achieve personal comfort as an ordinary person and analyze the public's response to the comic strip "Nyaman dan Sederhana" with the study of symbolic interactionism so that the comic can influence people's mindset. This research is a qualitative research with a literature study approach. Data collection techniques were carried out by reviewing books, journals, literature, notes, articles, and documents relevant to the focus of the research. The research method uses Miles and Huberman. The results showed the pros and cons of the community's response to the concept of stoicism in the comic and how global culture influenced the response.Keywords: globalization, culture, comics, symbolic interactionism, stoicism